Bridge deck waterproof material and preparation method thereof
By using modifiers such as fluorosilicon-type thermoplastic polyurethane elastomers and nanomaterials in bridge deck waterproof materials, the shortcomings of existing materials in low-temperature crack resistance, high temperature resistance and anti-aging properties have been solved, and higher bond strength and longer service life have been achieved.
Patent Information
- Application Number
- CN202510360637.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-26
AI Technical Summary
The existing bridge deck waterproof materials have shortcomings in low temperature and crack resistance, high temperature resistance and aging resistance, and have a short service life.
The combination of fluorosilicone thermoplastic polyurethane elastomer, vinyl hydroxy silicone oil, SBR rubber powder and reinforcement materials is used to modify the asphalt through copolymerization reaction and the introduction of nanomaterials to improve its bonding strength and weather resistance.
It significantly improves the bonding strength, low-temperature crack resistance, high-temperature resistance and aging resistance of bridge deck waterproof materials, extends the service life, simplifies the process flow, and reduces production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of waterproof materials, and in particular to a bridge deck waterproof material and a preparation method thereof. Background Art
[0002] As an important transportation hub, bridge deck waterproofing is of vital importance. Bridge decks are exposed to the natural environment for a long time and are subject to erosion by rainwater, snow-melting agents, etc. If the waterproofing measures are not appropriate, moisture will penetrate into the concrete, causing steel bars to rust and reducing the durability and safety of the bridge structure. In order to solve the bridge deck waterproofing problem, the current common practice is to lay a waterproof layer on the bridge deck. The waterproof layer is usually made of special bridge deck waterproofing materials. The performance of the waterproof layer directly affects the waterproofing effect, which is crucial to improving the safety and durability of the bridge and extending its service life.
[0003] At present, bridge deck waterproofing materials mainly include epoxy asphalt, hot-melt rubber asphalt, etc. However, although epoxy asphalt has excellent bonding properties and impermeability, its construction temperature is high (usually above 150°C), which can easily lead to construction damage and environmental pollution, and has high energy consumption. Although hot-melt rubber asphalt has low cost and good flexibility, it has problems such as high-temperature softening and deformation (softening point ≤ 60°C), low-temperature brittle cracking and insufficient crack resistance, and its bonding strength is only 1 / 3 of that of epoxy asphalt, which cannot meet the needs of heavy-load traffic. In addition, other types of bridge deck waterproofing materials on the market also have more or less technical defects such as unsatisfactory anti-breakage ability, insufficient waterproof performance, crack resistance and anti-aging performance, high temperature resistance still needs to be further improved, and short service life.
[0004] In order to solve the above problems, the Chinese invention patent with the authorization announcement number CN112646546B discloses a bridge deck waterproof material, which is made of the following components by weight: 10-20 parts of polyurethane with a vinyl ether end group, 60-70 parts of asphalt, 5-8 parts of 2,4-diamino-6-diallylamino-1,3,5-triazine, 3-5 parts of p-toluenesulfonic acid, 15-25 parts of carboxyl-terminated SBS, and 5-10 parts of functional copolymer; the functional copolymer is a copolymer made by copolymerization of allyl pentafluorobenzene, vinyl triethoxysilane, 1-allyl-3-methyl imidazole chloride, and allyl glycidyl ether. The invention also provides a preparation method of the bridge deck waterproof material. The bridge deck waterproof material disclosed in the invention has a significant waterproof effect, good comprehensive performance, high bonding strength, good high temperature resistance, anti-aging performance and performance stability, and long service life. However, its low temperature resistance and crack resistance still need to be further improved.
[0005] It can be seen that the development of a bridge deck waterproof material with high bonding strength, good low-temperature and crack resistance, good high-temperature resistance and aging resistance, excellent waterproof performance and long service life and its preparation method meet the market demand, have broad market value and application prospects, and are of great significance to promoting the development of the bridge deck material field. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a bridge deck waterproof material and a preparation method thereof which has high bonding strength, good low temperature resistance and crack resistance, good high temperature resistance and aging resistance, excellent waterproof performance and long service life.
[0007] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is a bridge deck waterproof material, which is made of the following raw materials in parts by weight: 15-22 parts of fluorosilicone thermoplastic polyurethane elastomer, 65-72 parts of asphalt, 3-5 parts of cellulose nanocrystals, 5-8 parts of 2-naphthylamine-4,8-disulfonic acid, 0.8-1.5 parts of phosphorus pentoxide, 0.5-0.8 parts of polyphosphoric acid, 4-6 parts of vinyl hydroxy silicone oil, 3-5 parts of SBR rubber powder, 1-2 parts of coupling agent, 5-8 parts of reinforcing material, 1-3 parts of 1,3,5-triglycidyl-S-triazinetrione, 1-2 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 3-5 parts of plasticizer, 1-3 parts of anti-aging agent, and 0.1-0.3 parts of initiator.
[0008] Furthermore, there is no special requirement for the source of the fluorosilicone thermoplastic polyurethane elastomer. In one embodiment of the present invention, the fluorosilicone thermoplastic polyurethane elastomer is made according to the method of Example 6 of Chinese invention patent with authorization publication number CN111154064B.
[0009] Preferably, the asphalt is at least one of ordinary heavy traffic 70# asphalt, ordinary heavy traffic 90# asphalt, and 110# road asphalt.
[0010] Preferably, the cellulose nanocrystals have a length of 100-500 nm and a diameter of 20-100 nm, and are provided by Beijing Nanosun Technology Co., Ltd.
[0011] Preferably, the vinyl hydroxy silicone oil has a hydroxyl content of 6±0.5 mol%, a vinyl content of 6±0.5 mol%, and a viscosity of ≤33 mm 2 / s, provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.
[0012] Preferably, the particle size of the SBR rubber powder is 20 mesh, which is provided by Jinan Bitu Chemical.
[0013] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.
[0014] Preferably, the reinforcing material is a mixture of nano-boron fiber, wollastonite and fly ash in a mass ratio of 1:(0.8-1.2):(1-3).
[0015] Preferably, the diameter of the nano-boron fiber is 300-500 nm, and the aspect ratio is (15-20):1; the particle size of the wollastonite is 500-800 mesh; and the particle size of the fly ash is 400-600 mesh.
[0016] Preferably, the plasticizer is epoxidized soybean oil; the antioxidant is at least one of antioxidant RD and antioxidant 4020; and the initiator is dicumyl peroxide.
[0017] Another object of the present invention is to provide a method for preparing the bridge deck waterproof material, comprising the following steps: heating asphalt to 170-180°C, adding fluorosilicone thermoplastic polyurethane elastomer and SBR rubber powder, stirring and reacting at a speed of 900-1500r / min for 1-3 hours, then adding cellulose nanocrystals, coupling agent, reinforcing material, plasticizer, anti-aging agent, 2-naphthylamine-4,8-disulfonic acid, phosphorus pentoxide, polyphosphoric acid, (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1,3,5-triglycidyl-S-triazinetrione, vinyl hydroxy silicone oil and initiator in sequence, continuing stirring for 1-2 hours, and starting the colloid mill for 1-2 hours to obtain the bridge deck waterproof material.
[0018] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0019] (1) The preparation method of the bridge deck waterproof material disclosed in the present invention has simple process, convenient operation and control, high preparation efficiency and finished product qualification rate, strong equipment versatility, greatly reduced equipment investment and maintenance costs, easy large-scale industrial production, and high promotion and application value.
[0020] (2) The bridge deck waterproof material disclosed in the present invention is made of the following raw materials in parts by weight: 15-22 parts of fluorosilicone thermoplastic polyurethane elastomer, 65-72 parts of asphalt, 3-5 parts of cellulose nanocrystals, 5-8 parts of 2-naphthylamine-4,8-disulfonic acid, 0.8-1.5 parts of phosphorus pentoxide, 0.5-0.8 parts of polyphosphoric acid, 4-6 parts of vinyl hydroxy silicone oil, 3-5 parts of SBR rubber powder, 1-2 parts of coupling agent, 5-8 parts of reinforcing material, 1-3 parts of 1,3,5-triglycidyl-S-triazinetrione, 1-2 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 3-5 parts of plasticizer, 1-3 parts of anti-aging agent, and 0.1-0.3 parts of initiator. Through the mutual cooperation and joint action of various raw materials, the bridge deck waterproof material has high bonding strength, good low temperature crack resistance, high temperature resistance and anti-aging performance, excellent waterproof performance and long service life. For the first time, the asphalt is modified by fluorosilicone thermoplastic polyurethane elastomer, vinyl hydroxy silicone oil, SBR rubber powder and reinforcing materials at the same time, which can significantly improve the high temperature stability, low temperature crack resistance and fatigue resistance of asphalt; enhance the adhesion of asphalt, and then improve the water resistance, chemical corrosion resistance and anti-aging performance of asphalt.
[0021] (3) The bridge deck waterproof material disclosed in the present invention introduces cellulose nanocrystals and uses a mixture of nano-boron fibers, wollastonite and fly ash in a mass ratio of 1:(0.8-1.2):(1-3) as a reinforcing material, which can significantly improve the crack resistance and impermeability, thereby improving the waterproof effect; the sulfonic acid group on 2-naphthylamine-4,8-disulfonic acid can not only promote the grafting reaction between raw materials containing vinyl functional groups and asphalt (cations under acidic conditions), so that these raw materials are connected to asphalt in the form of chemical bonds, but also, under the catalytic action of phosphorus pentoxide and polyphosphoric acid, the sulfonic acid group can also react chemically with raw materials containing benzene rings; the amino group on 2-naphthylamine-4,8-disulfonic acid can also react with 1,3,5-triglyceride The epoxy group on the oil-S-triazinetrione undergoes a chemical reaction, and a variety of interpenetrating network types are introduced into the bridge deck material at the same time, which can effectively improve the comprehensive performance and performance stability of the bridge deck material, so that the bridge deck material has high bonding strength, good low-temperature crack resistance, high-temperature resistance and anti-aging performance, excellent waterproof performance and long service life; (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, vinyl hydroxy silicone oil and 1,3,5-triglycidyl-S-triazinetrione introduce fluorine-containing structure, siloxane structure and triazone structure respectively, which, under the multiple effects of electronic effect, steric effect and conjugation effect, make the bridge deck material have better anti-aging and waterproof performance and longer service life.
[0022] (4) The bridge deck waterproof material disclosed in the present invention can effectively improve the construction performance of the material through the reasonable selection of composition formula and preparation process parameters, so that it has high bonding strength, good low temperature resistance and crack resistance, good high temperature resistance and anti-aging performance, excellent waterproof performance and long service life. DETAILED DESCRIPTION
[0023] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0024] Example 1, a bridge deck waterproof material, is made of the following raw materials in parts by weight: 15 parts of fluorosilicone thermoplastic polyurethane elastomer, 65 parts of asphalt, 3 parts of cellulose nanocrystals, 5 parts of 2-naphthylamine-4,8-disulfonic acid, 0.8 parts of phosphorus pentoxide, 0.5 parts of polyphosphoric acid, 4 parts of vinyl hydroxy silicone oil, 3 parts of SBR rubber powder, 1 part of coupling agent, 5 parts of reinforcing material, 1 part of 1,3,5-triglycidyl-S-triazinetrione, 1 part of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 3 parts of plasticizer, 1 part of antioxidant, and 0.1 part of initiator.
[0025] The fluorosilicone thermoplastic polyurethane elastomer is made according to the method of Example 6 of the Chinese invention patent with the authorization publication number CN111154064B; the asphalt is ordinary heavy cross-linked 70# asphalt; the length of the cellulose nanocrystal is 100-500nm, the diameter is 20-100nm, and it is provided by Beijing Naxun Technology Co., Ltd.; the hydroxyl content of the vinyl hydroxy silicone oil is 6±0.5mol%, the vinyl content is 6±0.5mol%, and the viscosity is ≤33mm 2 / s, provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.; the particle size of the SBR rubber powder is 20 mesh, provided by Jinan Bitu Chemical; the coupling agent is silane coupling agent KH550; the reinforcing material is a mixture of nano-boron fiber, wollastonite and fly ash in a mass ratio of 1:0.8:1; the diameter of the nano-boron fiber is 300nm, and the aspect ratio is 15:1; the particle size of the wollastonite is 500 mesh; the particle size of the fly ash is 400 mesh; the plasticizer is epoxidized soybean oil; the anti-aging agent is anti-aging agent RD; the initiator is diisopropylbenzene peroxide.
[0026] A preparation method of the bridge deck waterproof material comprises the following steps: heating asphalt to 170°C, adding fluorosilicone thermoplastic polyurethane elastomer and SBR rubber powder, stirring and reacting at a speed of 900 r / min for 1 hour, then sequentially adding cellulose nanocrystals, coupling agent, reinforcing material, plasticizer, anti-aging agent, 2-naphthylamine-4,8-disulfonic acid, phosphorus pentoxide, polyphosphoric acid, (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1,3,5-triglycidyl-S-triazinetrione, vinyl hydroxy silicone oil and initiator, continuing stirring for 1 hour, starting the colloid mill for 1 hour, and obtaining the bridge deck waterproof material.
[0027] Example 2, a bridge deck waterproof material, is made of the following raw materials in parts by weight: 17 parts of fluorosilicone thermoplastic polyurethane elastomer, 67 parts of asphalt, 3.5 parts of cellulose nanocrystals, 6 parts of 2-naphthylamine-4,8-disulfonic acid, 1 part of phosphorus pentoxide, 0.6 parts of polyphosphoric acid, 4.5 parts of vinyl hydroxy silicone oil, 3.5 parts of SBR rubber powder, 1.2 parts of coupling agent, 6 parts of reinforcing material, 1.5 parts of 1,3,5-triglycidyl-S-triazinetrione, 1.2 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 3.5 parts of plasticizer, 1.5 parts of anti-aging agent, and 0.15 parts of initiator.
[0028] The fluorosilicone thermoplastic polyurethane elastomer is made according to the method of Example 6 of the Chinese invention patent with the authorization publication number CN111154064B; the asphalt is ordinary heavy cross-linked 70# asphalt; the length of the cellulose nanocrystal is 100-500nm, the diameter is 20-100nm, and it is provided by Beijing Naxun Technology Co., Ltd.; the hydroxyl content of the vinyl hydroxy silicone oil is 6±0.5mol%, the vinyl content is 6±0.5mol%, and the viscosity is ≤33mm 2 / s, provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.; the particle size of the SBR rubber powder is 20 mesh, provided by Jinan Bitu Chemical; the coupling agent is silane coupling agent KH560; the reinforcing material is a mixture of nano-boron fiber, wollastonite and fly ash in a mass ratio of 1:0.9:1.5; the diameter of the nano-boron fiber is 350nm, and the aspect ratio is 17:1; the particle size of the wollastonite is 600 mesh; the particle size of the fly ash is 450 mesh; the plasticizer is epoxidized soybean oil; the anti-aging agent is antioxidant 4020; the initiator is diisopropylbenzene peroxide.
[0029] A preparation method of the bridge deck waterproof material comprises the following steps: heating asphalt to 173°C, adding fluorosilicone thermoplastic polyurethane elastomer and SBR rubber powder, stirring and reacting at a speed of 1100 r / min for 1.5 hours, then sequentially adding cellulose nanocrystals, coupling agent, reinforcing material, plasticizer, anti-aging agent, 2-naphthylamine-4,8-disulfonic acid, phosphorus pentoxide, polyphosphoric acid, (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1,3,5-triglycidyl-S-triazinetrione, vinyl hydroxy silicone oil and initiator, continuing stirring for 1.3 hours, starting the colloid mill for 1.3 hours, and obtaining the bridge deck waterproof material.
[0030] Example 3, a bridge deck waterproof material, is made of the following raw materials in parts by weight: 19 parts of fluorosilicone thermoplastic polyurethane elastomer, 69 parts of asphalt, 4 parts of cellulose nanocrystals, 6.5 parts of 2-naphthylamine-4,8-disulfonic acid, 1.2 parts of phosphorus pentoxide, 0.65 parts of polyphosphoric acid, 5 parts of vinyl hydroxy silicone oil, 4 parts of SBR rubber powder, 1.5 parts of coupling agent, 6.5 parts of reinforcing material, 2 parts of 1,3,5-triglycidyl-S-triazinetrione, 1.5 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 4 parts of plasticizer, 2 parts of antioxidant, and 0.2 parts of initiator.
[0031] The fluorosilicone thermoplastic polyurethane elastomer is made according to the method of Example 6 of the Chinese invention patent with the authorization publication number CN111154064B; the asphalt is ordinary heavy cross-linked 70# asphalt; the length of the cellulose nanocrystal is 100-500nm, the diameter is 20-100nm, and it is provided by Beijing Naxun Technology Co., Ltd.; the hydroxyl content of the vinyl hydroxy silicone oil is 6±0.5mol%, the vinyl content is 6±0.5mol%, and the viscosity is ≤33mm 2 / s, provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.; the particle size of the SBR rubber powder is 20 mesh, provided by Jinan Bitu Chemical; the coupling agent is silane coupling agent KH570; the reinforcing material is a mixture of nano-boron fiber, wollastonite and fly ash in a mass ratio of 1:1:2; the diameter of the nano-boron fiber is 400nm, and the aspect ratio is 18:1; the particle size of the wollastonite is 650 mesh; the particle size of the fly ash is 500 mesh; the plasticizer is epoxidized soybean oil; the anti-aging agent is anti-aging agent RD; the initiator is diisopropylbenzene peroxide.
[0032] A preparation method of the bridge deck waterproof material comprises the following steps: heating asphalt to 175°C, adding fluorosilicone thermoplastic polyurethane elastomer and SBR rubber powder, stirring and reacting at a speed of 1300 r / min for 2 hours, then sequentially adding cellulose nanocrystals, coupling agent, reinforcing material, plasticizer, anti-aging agent, 2-naphthylamine-4,8-disulfonic acid, phosphorus pentoxide, polyphosphoric acid, (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1,3,5-triglycidyl-S-triazinetrione, vinyl hydroxy silicone oil and initiator, continuing stirring for 1.5 hours, starting the colloid mill for 1.5 hours, and obtaining the bridge deck waterproof material.
[0033] Example 4, a bridge deck waterproof material, is made of the following raw materials in parts by weight: 21 parts of fluorosilicone thermoplastic polyurethane elastomer, 70 parts of asphalt, 4.5 parts of cellulose nanocrystals, 7.5 parts of 2-naphthylamine-4,8-disulfonic acid, 1.4 parts of phosphorus pentoxide, 0.75 parts of polyphosphoric acid, 5.5 parts of vinyl hydroxy silicone oil, 4.5 parts of SBR rubber powder, 1.8 parts of coupling agent, 7.5 parts of reinforcing material, 2.5 parts of 1,3,5-triglycidyl-S-triazinetrione, 1.8 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 4.5 parts of plasticizer, 2.5 parts of anti-aging agent, and 0.25 parts of initiator.
[0034] The fluorosilicone thermoplastic polyurethane elastomer is made according to the method of Example 6 of the Chinese invention patent with the authorization publication number CN111154064B; the asphalt is ordinary heavy cross-linked 70# asphalt; the length of the cellulose nanocrystal is 100-500nm, the diameter is 20-100nm, and it is provided by Beijing Naxun Technology Co., Ltd.; the hydroxyl content of the vinyl hydroxy silicone oil is 6±0.5mol%, the vinyl content is 6±0.5mol%, and the viscosity is ≤33mm 2 / s, provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.; the particle size of the SBR rubber powder is 20 mesh, provided by Jinan Bitu Chemical; the coupling agent is a mixture of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570 in a mass ratio of 1:2:3; the reinforcing material is a mixture of nano-boron fiber, wollastonite, and fly ash in a mass ratio of 1:1.1:2.5; the diameter of the nano-boron fiber is 450nm, and the aspect ratio is 19:1; the particle size of the wollastonite is 750 mesh; the particle size of the fly ash is 550 mesh; the plasticizer is epoxidized soybean oil; the anti-aging agent is a mixture of anti-aging agent RD and anti-aging agent 4020 in a mass ratio of 3:5; the initiator is diisopropylbenzene peroxide.
[0035] A preparation method of the bridge deck waterproof material comprises the following steps: heating asphalt to 178° C., adding fluorosilicone thermoplastic polyurethane elastomer and SBR rubber powder, stirring and reacting at a speed of 1400 r / min for 2.5 hours, then sequentially adding cellulose nanocrystals, coupling agent, reinforcing material, plasticizer, anti-aging agent, 2-naphthylamine-4,8-disulfonic acid, phosphorus pentoxide, polyphosphoric acid, (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1,3,5-triglycidyl-S-triazinetrione, vinyl hydroxy silicone oil and initiator, continuing stirring for 1.8 hours, starting the colloid mill for 1.8 hours, and obtaining the bridge deck waterproof material.
[0036] Example 5, a bridge deck waterproof material, is made of the following raw materials in parts by weight: 22 parts of fluorosilicone thermoplastic polyurethane elastomer, 72 parts of asphalt, 5 parts of cellulose nanocrystals, 8 parts of 2-naphthylamine-4,8-disulfonic acid, 1.5 parts of phosphorus pentoxide, 0.8 parts of polyphosphoric acid, 6 parts of vinyl hydroxy silicone oil, 5 parts of SBR rubber powder, 2 parts of coupling agent, 8 parts of reinforcing material, 3 parts of 1,3,5-triglycidyl-S-triazinetrione, 2 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 5 parts of plasticizer, 3 parts of antioxidant, and 0.3 parts of initiator.
[0037] The fluorosilicone thermoplastic polyurethane elastomer is made according to the method of Example 6 of the Chinese invention patent with the authorization publication number CN111154064B; the asphalt is ordinary heavy cross-linked 70# asphalt; the length of the cellulose nanocrystal is 100-500nm, the diameter is 20-100nm, and it is provided by Beijing Naxun Technology Co., Ltd.; the hydroxyl content of the vinyl hydroxy silicone oil is 6±0.5mol%, the vinyl content is 6±0.5mol%, and the viscosity is ≤33mm 2 / s, provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.; the particle size of the SBR rubber powder is 20 mesh, provided by Jinan Bitu Chemical; the coupling agent is silane coupling agent KH550; the reinforcing material is a mixture of nano-boron fiber, wollastonite and fly ash in a mass ratio of 1:1.2:3; the diameter of the nano-boron fiber is 500nm, and the aspect ratio is 20:1; the particle size of the wollastonite is 800 mesh; the particle size of the fly ash is 600 mesh; the plasticizer is epoxidized soybean oil; the anti-aging agent is anti-aging agent RD; the initiator is diisopropylbenzene peroxide.
[0038] A preparation method of the bridge deck waterproof material comprises the following steps: heating asphalt to 180°C, adding fluorosilicone thermoplastic polyurethane elastomer and SBR rubber powder, stirring and reacting at a speed of 1500r / min for 3 hours, then sequentially adding cellulose nanocrystals, coupling agent, reinforcing material, plasticizer, anti-aging agent, 2-naphthylamine-4,8-disulfonic acid, phosphorus pentoxide, polyphosphoric acid, (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1,3,5-triglycidyl-S-triazinetrione, vinyl hydroxy silicone oil and initiator, continuing stirring for 2 hours, starting the colloid mill for 2 hours, and obtaining the bridge deck waterproof material.
[0039] Comparative Example 1, a bridge deck waterproof material and a preparation method thereof, is substantially the same as Example 1, except that cellulose nanocrystals and 2-naphthylamine-4,8-disulfonic acid are not added.
[0040] Comparative Example 2, a bridge deck waterproof material and a preparation method thereof, is basically the same as Example 1, except that (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate and 1,3,5-triglycidyl-S-triazinetrione are not added.
[0041] In order to further illustrate the beneficial technical effects of the bridge deck waterproof materials involved in each embodiment of the present invention, relevant performance tests were conducted on the bridge deck waterproof materials involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows:
[0042] (1) Waterproof performance test method: Refer to GB / T 328.10-2007 "Test methods for building waterproof membranes Part 10: Waterproofness of asphalt and polymer waterproof membranes" for testing. Install the prepared test piece on the water-proof instrument, apply 0.5MPa water pressure for 24 hours, and observe whether there is water seepage on the surface of the test piece to judge the waterproof performance of the material.
[0043] (2) Low temperature flexibility test: refer to the low temperature flexibility test method in GB / T 328.14-2007 "Test methods for building waterproofing membranes Part 14: Test methods for low temperature flexibility of asphalt waterproofing membranes". Test the specimens at -24°C and observe whether there are cracks on the surface of the specimens. If at least 4 out of 5 specimens on a test surface are free of cracks, the test surface passes. If both the upper and lower test surfaces pass, the low temperature flexibility is qualified, otherwise it fails.
[0044] (3) High temperature stability test: Refer to the heat resistance test method in JCT 975-2005 "Waterproof coatings for roads and bridges" to conduct a heat resistance test. Observe whether the specimen has flow, sliding and dripping after the test under the test condition of 160℃.
[0045] (4) Bond strength test: Refer to the test method for bond strength in JCT 975-2005 "Waterproof coatings for roads and bridges" and retain two decimal places for the test results.
[0046] (5) Heat aging and salt resistance test: refer to the mass increase in heat aging test and the mass loss in salt treatment in JCT 975-2005 "Waterproof coatings for roads and bridges" for measurement.
[0047] Table 1 Test results of bridge deck waterproofing material performance
[0048]
[0049] As can be seen from Table 1, the bridge deck waterproof material involved in the embodiment of the present invention has better waterproofness, low-temperature crack resistance and high-temperature stability, better heat aging resistance and salt resistance, and stronger bonding strength than the comparative example product; the combined use of cellulose nanocrystals, 2-naphthylamine-4,8-disulfonic acid, (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate and 1,3,5-triglycidyl-S-triazinetrione is beneficial to improving the above properties.
[0050] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A bridge deck waterproof material, characterized in that: The invention is prepared from the following raw materials in parts by weight: 15-22 parts of fluorosilicone thermoplastic polyurethane elastomer, 65-72 parts of asphalt, 3-5 parts of cellulose nanocrystals, 5-8 parts of 2-naphthylamine-4,8-disulfonic acid, 0.8-1.5 parts of phosphorus pentoxide, 0.5-0.8 parts of polyphosphoric acid, 4-6 parts of vinyl hydroxy silicone oil, 3-5 parts of SBR rubber powder, 1-2 parts of coupling agent, 5-8 parts of reinforcing material, 1-3 parts of 1,3,5-triglycidyl-S-triazinetrione, 1-2 parts of (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 3-5 parts of plasticizer, 1-3 parts of anti-aging agent and 0.1-0.3 parts of initiator.
2. The bridge deck waterproof material according to claim 1, characterized in that: The asphalt is at least one of ordinary heavy traffic 70# asphalt, ordinary heavy traffic 90# asphalt, and 110# road asphalt.
3. The bridge deck waterproof material according to claim 1, characterized in that: The length of the cellulose nanocrystal is 100-500nm and the diameter is 20-100nm; the hydroxyl content of the vinyl hydroxy silicone oil is 6±0.5mol%, the vinyl content is 6±0.5mol%, and the viscosity is ≤33mm 2 / s.
4. The bridge deck waterproof material according to claim 1, characterized in that: The particle size of the SBR rubber powder is 20 meshes; the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.
5. The bridge deck waterproof material according to claim 1, characterized in that: The reinforcing material is a mixture of nano boron fiber, wollastonite and fly ash in a mass ratio of 1:(0.8-1.2):(1-3).
6. The bridge deck waterproof material according to claim 5, characterized in that: The diameter of the nano boron fiber is 300-500nm, and the aspect ratio is (15-20):1; the particle size of the wollastonite is 500-800 mesh; and the particle size of the fly ash is 400-600 mesh.
7. The bridge deck waterproof material according to claim 1, characterized in that: The plasticizer is epoxidized soybean oil; the antioxidant is at least one of antioxidant RD and antioxidant 4020; and the initiator is dicumyl peroxide.
8. A method for preparing a bridge deck waterproof material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: heating the asphalt to 170-180°C, adding fluorosilicone thermoplastic polyurethane elastomer and SBR rubber powder, stirring the mixture at a speed of 900-1500 r / min for reaction for 1-3 hours, then sequentially adding cellulose nanocrystals, coupling agent, reinforcing material, plasticizer, anti-aging agent, 2-naphthylamine-4,8-disulfonic acid, phosphorus pentoxide, polyphosphoric acid, (perfluoropropane-2,2-diyl)bis(4,1-phenylene) diacrylate, 1,3,5-triglycidyl-S-triazinetrione, vinyl hydroxy silicone oil and initiator, continuing stirring for 1-2 hours, starting the colloid mill for 1-2 hours, and obtaining the bridge deck waterproof material.
Citation Information
Patent Citations
A fluorosilicone thermoplastic polyurethane elastomer and its preparation method
CN111154064B
A bridge deck waterproofing material and its preparation method
CN112646546B
Asphalt regeneration agent as well as preparation method and application thereof
CN104610768A
Bridge deck waterproof material and preparation method thereof
CN112646546A
High-viscosity modified asphalt waterproof coiled material and preparation method thereof
CN113684696A